BHAKTI DAN KOMUNIKASI SPIRITUAL DI ERA DIGITAL: KAJIAN LITERATUR ATAS TRANSFORMASI RITUAL DAN DEVOSI HINDU DI PLATFORM ONLINE - Eni Kusti Rahayu (Fakultas Dharma Duta dan Brahma Widya, 2025)
Digital transformation has permeated various aspects of life, including spiritual practices within Hinduism, a tradition rich in the values of bhakti (devotion). This article explores the transformation of bhakti-based spiritual communication in the context of digital media, particularly through practices such as live-streamed puja, spiritual content on YouTube, and other online platforms. Utilizing a qualitative, literature-based approach, this study integrates classical Hindu texts such as the Bhagavata Purana and Narada Bhakti Sutra with contemporary academic literature on digital religious communication. The findings indicate that while the form and medium of ritual delivery have undergone significant transformation, the core values of bhakti—including divine love, selfless service (seva), and spiritual connection—remain preserved. Moreover, digital connectivity expands the reach of devotional practices, enabling spiritual participation across geographical and generational boundaries. Virtual communities actively contribute to shaping inclusive and adaptive digital worship spaces. Thus, digital bhakti not only represents a new mode of spirituality but also affirms the resilience and adaptability of Hindu teachings in the technological age. Keywords: Bhakti, Spiritual Communication, Online Puja, Digital Hinduism, Devotion, YouTube Spirituality